Postsurgical Presentation of Zollinger–Ellison Syndrome After Resection of Endometrioid Neuroendocrine Tumor. Issue 5 (11th May 2021) - Almuhaidb, Aymen; Davidson, Nicholas O.
ABSTRACT: Zollinger–Ellison syndrome is a functional neuroendocrine tumor with inappropriate gastrin secretion and hyperchlorhydria causing severe peptic ulcer disease and chronic diarrhea. Although 70% of primary gastrinomas occur in the region of the duodenum, the diagnosis and localization of gastrinomas can be challenging because of small lesions that may arise functionally as lymph node metastases at initial presentation. We report a 76-year-old woman presenting with Zollinger–Ellison syndrome several months after surgical resection of endometrioid small cell neuroendocrine carcinoma and endometrioid adenocarcinoma.